Structural Performance Analysis of HDPE and ABS Formwork Designs Using Finite Element Analysis - zulkarnaen zulkarnaen; Harus Laksana Guntur; Riyki Apriandi (Naval Architecture Department, Kalimantan Institut of Technology, 2026)
This study evaluates the structural performance of polymer-based formwork systems using HDPE and ABS materials through numerical simulation based on the Finite Element Method (FEM). Rib design variations, including square, round, and honeycomb, were analyzed by considering key parameters such as deformation, elastic strain, equivalent stress, and safety factor. The applied loading conditions consisted of hydrostatic pressure from fresh concrete and additional loads due to the accumulation of upper structural segments. The results show that ABS exhibits higher stiffness, leading to lower deformation and elastic strain values compared to HDPE. Nevertheless, HDPE demonstrates competitive performance, offering advantages in ductility, environmental resistance, and lower weight. Among the design configurations, the honeycomb structure provides the most efficient load distribution and minimizes stress concentration more effectively than square and round designs. All models, for both HDPE and ABS materials, satisfy structural safety requirements with safety factor values greater than one. Therefore, the combination of ABS material and honeycomb rib design is recommended as an optimal solution for polymer-based formwork applications, while HDPE remains a viable alternative for applications requiring enhanced flexibility and environmental durability.